Dynamics of coral rubble on reef flats: from individual clast mobilisation to rubble strip morphological change - Aitana Gea-Neuhaus; Tim Scott; Gerd Masselink; Ana Vila-Concejo; Paul S. Kench; Mathilde Lindhart; Floortje E. Roelvink; Tom Hamilton; Ke Lin; Xianfeng Wang (Marine Geology, 2026)

Wave, light, and dissolved oxygen exposures drive novel coastal eelgrass (Zostera pacifica) transplant performance - Rilee D. Sanders; Adam K. Obaza; Benjamin C. Grime; Mathilde Lindhart; Luke P. Miller; Kristen E. Elsmore; Olivia C. Carmack; Tom K. Ford; James J. Leichter (Frontiers in Marine Science, 2024)
The high ecological and economic value of seagrass has been long recognized, with these foundational habitats providing myriad ecosystem services. Yet through cumulative anthropogenic impacts, seagrasses are exhibiting extensive declines globally. A litany of studies and active restoration trials have demonstrated practical methodologies to restore seagrass habitats and effectively return critical habitat functions to degraded coastal zone systems worldwide. Seagrass loss along the U.S. West Coast has precipitated decades of seagrass protection, conservation, and restoration efforts. Yet, mitigation transplanting efforts have prioritized Zostera marina (narrow-leaved eelgrass) in shallow, protected environments, while a dearth of information is available on species inhabiting offshore islands and exposed mainland coasts. In this study, we conducted a novel transplant of Zostera pacifica , a wide-leaved species found in depths of 7 – 20 m along the offshore islands and mainland coast of California. Transplants were conducted at three geographically distinct sites in Santa Monica Bay, coupled with continuous monitoring of biophysical parameters providing insight into physical drivers at transplant and donor sites. Utilizing in situ data, and environmental thresholds adapted from the literature for Z. marina , we performed exposure analyses to evaluate factors influencing Z. pacifica transplant performance. Exceedances of threshold values for environmental parameters, specifically, wave exposure and near-bed flow speeds ( H rms > 0.59 m and U rms > 0.1 m s -1 ), photosynthetically active radiation (< 3 and > 5 mol m -2 day -1 ) and dissolved oxygen (< 3 mg O 2 L -1 ) exposure impacted transplant survivorship. These results suggest Z. pacifica persist in biophysically dynamic conditions and are sensitive to exceedances of thresholds, underlining the importance of pre-transplant site-selection processes to this species. These data represent the first holistic study of Z. pacifica transplanting on an exposed mainland coast, which provides a view into the baseline environmental envelopes within existing Z. pacifica habitat, and further, may serve as a model for investigating scalable open coast seagrass restoration for temperate regions.

Remote reef cryptobenthic diversity: Integrating autonomous reef monitoring structures and in situ environmental parameters - Margaux Steyaert; Mathilde Lindhart; Alexandra Khrizman; Robert B. Dunbar; Michael B. Bonsall; David A. Mucciarone; Emma Ransome; Nadia Santodomingo; Paige Winslade; Catherine E. I. Head (Frontiers in Marine Science, 2022)
Coral reef sessile organisms inhabiting cryptic spaces and cavities of the reef matrix perform vital and varied functional roles but are often understudied in comparison to those on exposed surfaces. Here, we assess the composition of cryptobenthic taxa from three remote tropical reef sites (Central Indian Ocean) alongside a suite of in situ environmental parameters to determine if, or how, significant patterns of diversity are shaped by local abiotic factors. To achieve this, we carried out a point-count analysis of autonomous reef monitoring structure (ARMS) plate images and employed in situ instrumentation to recover long-term (12 months) profiles of flow velocity, wave heights, temperature, dissolved oxygen, and salinity, and short-term (3 weeks) profiles of light and pH. We recovered distinct environmental profiles between sampling sites and observed that ocean-facing reefs experienced frequent but short-lived cooling internal wave events and that these were key in shaping in situ temperature variability. By comparing temperature and wave height profiles recovered using in situ loggers with ex situ models, we discovered that global satellite products either failed to recover site-specific profiles or both over- and underestimated actual in situ conditions. We found that site choice and recruitment plate face (top or bottom) significantly impacted the percentage cover of bryozoans, gastropods, soft and calcified tube worms, as well as crustose coralline algae (CCA) and fleshy red, brown, and green encrusting macroalgae on ARMS. We observed significant correlations between the abundance of bryozoans, CCA, and colonial tunicates with lower mean temperature and higher mean dissolved oxygen profiles observed across sites. Red and brown encrusting macroalgae abundance correlated significantly with medium-to-high flow velocities and wave height profiles, as well as higher pH and dissolved oxygen. This study provides the first insight into cryptobenthic communities in the Chagos Archipelago marine-protected area and adds to our limited understanding of tropical reef sessile communities and their associations with environmental parameters in this region. With climate change accelerating the decline of reef ecosystems, integrating analyses of cryptobenthic organisms and in situ physicochemical factors are needed to understand how reef communities, if any, may withstand the impacts of climate change.

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)